2018
DOI: 10.1002/lary.27197
|View full text |Cite
|
Sign up to set email alerts
|

Earfold: A New Technique for Correction of the Shape of the Antihelix

Abstract: An absent or poorly defined antihelix often plays a central role in the perception of the prominent ear. A wide variety of otoplasty techniques have been described over the last 50 years that aim to reshape, create, or enhance the definition of the antihelix, which can, in turn, help to reduce the prominence of an ear. In addition to conventional suture and cartilage‐scoring techniques, a permanent implantable clip system (Earfold®) has recently become available that is placed using a minimally invasive approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(116 reference statements)
0
3
0
1
Order By: Relevance
“…In the years 2020 and 2021, 91 ears were http://dx.doi.org/10.52533/JOHS.2023.31011 treated using this method, and just one (1.1%) of those ears needed revision (13). Figure 1 shows antihelical fold creation with cartilagesparing techniques to lessen ear prominence (14). Ferzli et al reported that numerous improvements to the cartilage-sparing otoplasty procedure have been documented since it was first introduced.…”
Section: Cartilage-sparingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the years 2020 and 2021, 91 ears were http://dx.doi.org/10.52533/JOHS.2023.31011 treated using this method, and just one (1.1%) of those ears needed revision (13). Figure 1 shows antihelical fold creation with cartilagesparing techniques to lessen ear prominence (14). Ferzli et al reported that numerous improvements to the cartilage-sparing otoplasty procedure have been documented since it was first introduced.…”
Section: Cartilage-sparingmentioning
confidence: 99%
“…Similarly, Cihandide et al stated that the increased risk of hemorrhage, skin necrosis, and ear deformity associated with cartilage-cutting techniques has led to criticism of them and therefore cartilage-sparing techniques are preferred (22). Figure 3 illustrates the creation of an antihelical fold and the reduction of ear prominence by cartilage-cutting and sculpting techniques (14).…”
Section: Cartilage-cuttingmentioning
confidence: 99%
See 1 more Smart Citation
“…Su incidencia aproximada es del 5% en población caucásica y se transmite de forma autosómica dominante con penetrancia variable 3 . Las principales alteraciones que la producen son un antihélix desdoblado, hipertrofia de la concha auricular, concha profunda, rotación anterior de la concha o una combinación de éstas, siendo el antihélix desdoblado el 70% de los casos 4,5 .…”
Section: Introductionunclassified